Shared Habitat Distribution of Javan Hawk-eagle, Javan Leopard, and JavanGibbon in Gunung Halimun Salak National Park, Indonesia - Suyitno, Rofifah Aulia; Syartinilia; Mulyani, Yeni Aryati; Ario, Anton (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2026)
Gunung Halimun Salak National Park (NP) is recognized as an important habitat for rare or key species of Java Island such as the Javan Hawk-eagle, Javan leopard, and Javan gibbon. Although these species exhibit different movement patterns (aerial, arboreal, and terrestrial), their spatial overlap within the landscape suggests potential ecological interactions, particularly within the trophic structure which is rarely integrated before. This study aims to identify, describe, and provide recommendations for the management of key species shared habitats based on spatial approach. Spatial analysis was used to examine the distribution of shared habitats and their biophysical characteristics, including land cover, elevation, and slope. A literature and policy review was conducted to align the findings with existing Conservation Strategies and Action Plans, based on applicable regulations and NP zonation. The analysis reveals that habitat distribution within the NP is categorized into 28.78% two key species and 55.84% three key species shared habitat. Biophysically, key species shared habitat is primarily found in forested areas between 500–1,500 meters above sea level (masl), and mostly located on steep slope around 25–45%. In terms of Gunung Halimun Salak NP zonation, two key species and three key species habitats are mainly located within the core, forest, and use zones of the Gunung Halimun Salak NP. The recommendations are developed aligned with the Conservation Strategy and Action Plan, regulations, and NP zonation for the comprehensive and integrated habitat management strategies of the key species shared habitat.